Enhancing Social-Ecological Resilience in Indonesia: A Case of North Pekalongan District, Central Java - A. Artiningsih; Suratman Worosuprojo; R. Rijanta; Su Rito Hardoyo (Department of Urban and Regional Planning, Diponegoro University, 2016)
In the last eight years (2008-2016), some areas in the northern part of Pekalongan have been experiencing coastal inundation. There have been social, economic and physical disruptions caused by coastal inundation particularly on built environments, paddy fields, and fishpond. The capacity of these areas to provide support for community livelihood has decreased significantly. This accumulative environmental change leads to the emergence of vulnerable regions which are characterized by limited social and ecological capacity to respond hazards. In order to enhance the social-ecological resilience, it is necessary to identify how the community has elevated their capacity and improved their livelihood. This paper presents empirical evidence of various pathways on how the community has transformed their capacity to respond to the changing environment due to coastal inundation. Following case study approach, this paper explores how the community has learned from their experiences, knowledge, and efforts from the past, and transformed them into a better understanding to cope with, to adapt to, and to become resilient from coastal inundation. The research applied in-depth interviews involving key persons selected through purposive and snowballing samplings. They represented the most capable person in each sub-district whose important data and information related to coastal inundation at the individual, household, and community organization levels belong to. The scope of area observation was limited to six sub-districts adjacent to the coast in the North Pekalongan District. The results showed that social-ecological resilience is likely to enhance in a community with flexible networking building capability. Such networking is beneficial to spreading out the important information, novel knowledge and practical tools and solutions to the community. These are the key elements for new transformative pathways. However, there remain various community capacities with different achievements on transformative pathways necessary to the future empowerment initiatives. Only a few communities in Kandang Panjang Sub-district who have performed a short-term resilience due to their awareness on establishing social networking and several actions on environmental quality improvements.